2012
DOI: 10.1177/0363546511432711
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Radiographic Hip Abnormalities in Elite Soccer Players

Abstract: The prevalence of radiographic hip abnormalities in elite soccer athletes is considerable, particularly in young male athletes. The establishment of the prevalence of these findings represents the first step in identifying the relationship between radiographic abnormalities and injuries of the hip and groin in athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
162
4
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(186 citation statements)
references
References 30 publications
13
162
4
7
Order By: Relevance
“…Many studies have investigated the associations between sex and hip anatomy (Table 5) [5,9,17,29,37,46,52] and between the femoral and acetabular parameters measured in this study (Table 6) [1-3, 9, 14, 24, 31, 39, 46, 50, 52, 54]. Our findings agree with most of this literature but do conflict with two studies [2,54] that found no association between femoral and acetabular version (Table 6).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Many studies have investigated the associations between sex and hip anatomy (Table 5) [5,9,17,29,37,46,52] and between the femoral and acetabular parameters measured in this study (Table 6) [1-3, 9, 14, 24, 31, 39, 46, 50, 52, 54]. Our findings agree with most of this literature but do conflict with two studies [2,54] that found no association between femoral and acetabular version (Table 6).…”
Section: Discussionsupporting
confidence: 77%
“…For example, symptomatic dysplasia and excessive femoral anteversion are more common in females [18,20,35,49,54]. In several series of patients with FAI, women with symptomatic impingement had smaller cam deformities [17,20,24,37] but could present with worse preoperative scores for pain and function than men [23]. The associations between these various anatomic factors and how often they occur in a painful hip are unclear but if unaddressed at the time of surgery might explain failed hip preservation surgery.…”
Section: Introductionmentioning
confidence: 99%
“…This has led to increased interest in the early diagnosis of FAI via potential screening, especially in patients who are considered to be at high risk, such as elite athletes [10], athletes who participate in sports that have higher risks for changes in morphologic features of the hip [16,24], and siblings of patients with impingement [30]. Abnormalities of morphologic features that can lead to FAI include cam abnormality on the femoral side and/or pincer overcoverage on the acetabular side [15,33].…”
Section: Introductionmentioning
confidence: 99%
“…Zudem war bei 50 % (Frauen) bzw. 72 % (Männer) der in einer weiteren Studie untersuchten Profifußballer radiologisch eine Impingementdeformität nachzuweisen [9].…”
Section: Klinische Untersuchungunclassified